Response assessment criteria for brain metastases: proposal from the RANO group - Lin, Nancy; Lee, Eudocia Q; Aoyama, Hidefumi; Barani, Igor J; Barboriak, Daniel P; Baumert, Brigitta G; Bendszus, Martin; Brown, Paul D; Camidge, D Ross; Chang, Susan M; Dancey, Janet; de Vries, Elisabeth G E; et al. (The lancet. Oncology, 2015)
CNS metastases are the most common cause of malignant brain tumours in adults. Historically, patients with brain metastases have been excluded from most clinical trials, but their inclusion is now becoming more common. The medical literature is difficult to interpret because of substantial variation in the response and progression criteria used across clinical trials. The Response Assessment in Neuro-Oncology Brain Metastases (RANO-BM) working group is an international, multidisciplinary effort to develop standard response and progression criteria for use in clinical trials of treatment for brain metastases. Previous efforts have focused on aspects of trial design, such as patient population, variations in existing response and progression criteria, and challenges when incorporating neurological, neuro-cognitive, and quality-of-life endpoints into trials of patients with brain metastases. Here, we present our recommendations for standard response and progression criteria for the assessment of brain metastases in clinical trials. The proposed criteria will hopefully facilitate the development of novel approaches to this difficult problem by providing more uniformity in the assessment of CNS metastases across trials.